Resting heart rate and cardiovascular outcomes in patients with atrial fibrillation: CODE-AF registry. (19th May 2022) - Park, H; Yu, HT; Kim, TH; Park, J; Park, JK; Kang, KW; Shim, J; Kim, JB; Kim, J; Choi, EK; Park, HW; Lee, YS; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: The prognostic significance of resting heart rate and its therapeutic target in atrial fibrillation (AF) is uncertain. Purpose: The aim of this study was to investigate the relationships between resting heart rate and cardiovascular outcomes in patients with AF. Methods: A total of 8, 886 patients with AF was included from the COmparison study of Drugs for symptom control and complication prEvention of AF (CODE-AF) registry. Patients were categorized according to baseline heart rate, and cardiovascular outcomes were accessed during a median follow-up of 30 months. The primary outcome was a composite of cardiovascular death, hospitalization due to heart failure, and myocardial infarction/critical limb ischemia. Results: Compared to heart rate ≥100 beats per minute (bpm), heart rate 80-99 bpm was associated with the lowest risk of primary outcome (adjusted hazard ratio [HR] 0.56, 95% confidence interval [CI] 0.40-0.79, p=0.001). In subgroup of patients with heart failure with preserved ejection fraction (HFpEF), heart rate between 80-99 bpm was associated with reduced risk of primary outcome compared to heart rate ≥100 bpm (HR 0.40, 95% CI 0.16-0.98, p=0.045). However, in patients with heart failure with reduced ejection fraction (HFrEF), there was no association between resting heart rate and cardiovascular outcomes (P for interaction 0.001). Conclusion: Resting heart rate was associated with cardiovascular outcomes in patients with AF, and those with a resting heart rate between 80-99 bpm had the lowest risk of adverse events. The impact of resting heart rate on adverse events persisted in patients with concomitant HFpEF but was not apparent in those with concomitant HFrEF.